The low dispersion synthetic spectra of cool giant stars - Belik, S. I.; Dragunova, A. V.; Komarov, N. S. (Одеські астрономічні публікації, 2017)
he mean energy distribution of cool giant stars was used for comparison with synthetic spectra. The synthetic spectra was calculated using the various grids of stellar rnodel atrnospheres.